Pelaksanaan Bimbingan Kelompok Untuk menumbuhkan Self Management dalam Belajar Siswa - Firman Gustiana; Isep Zaenal Arifin; Elly Marlina (Department of Islamic Guidance and Counseling, Faculty of Dakwah and Communication, UIN Sunan Gunung Djati Bandung, 2017)
The purpose of this study was to find out individual counseling services used by BK teachers at SMPN three Darangdan in reducing the problem of students skipping school and to know the process of implementing individual counseling services in reducing the problem of students skipping school, as well as to know the results achieved from individual counseling services in reducing the problem of students skipping school. The method used in this study is descriptive with a qualitative approach, describing the situation or event. Primary data were obtained with interviews and field notes. While secondary data seen from official documents, and reference books about individual counseling services at SMPN three Darangdan. Data analysis includes data reduction, data presentation, and conclusions. From the results of research indicate that, the implementation of individual counseling that includes counselor factors, counselors, methods and factors supporting facilities and facilities is good enough. Students after being given individual counseling services by BK teachers, students can change the behavior of the original students did not go to school or truancy after individual counseling students finally turned into a positive direction that is no longer skipping and the intensity of bolosnya in a month reduced. Tujuan penelitian ini adalah untuk mengetahui layanan konseling individu yang digunakan oleh guru BK di SMPN tiga Darangdan dalam mengurangi masalah siswa bolos sekolah dan untuk mengatahui proses pelaksanaan layanan konseling individu dalam mengurangi masalah siswa bolos sekolah, serta untuk mengetahui hasil yang dicapai dari layanan konseling individu dalam mengurangi masalah siswa bolos sekolah. Metode yang digunakan pada penelitian ini bersifat deskriftif dengan pendekatan kualitatif, memaparkan situasi atau peristiwa. Data primer diperoleh dengan wawancara dan catatan lapangan. Sedangkan data sekunder dilihat dari dokumen resmi, dan buku-buku referensi tentang layanan konseling individu di SMPN tiga Darangdan. Analisis data meliputi reduksi data, penyajian data, dan penarikan kesimpulan. Dari hasil penelitian menunjukkan bahwa, pelaksanaan konseling individu yang meliputi faktor konselor, konseli, metode maupun faktor-faktor pendukung sarana maupun fasilitas sudah cukup baik. Siswa setelah diberikan layanan konseling individu oleh guru BK, siswa dapat merubah perilakunya yang semula siswa tidak berangkat kesekolah atau bolos setelah dilakukan konseling individu akhirnya siswa menjadi berubah kearah positif yakni tidak lagi bolos dan intensitas bolosnya dalam sebulan berkurang.